Plymouth and Pungo Turnpike Road (Document (North Carolina. General Assembly), 1857)
January 16, 1857 letter of Governor Bragg, with attached letter from Matthew Shaw of the North Carolina Literary Fund, to the General Assembly. These letters indicated that various appropriations for the construction of the Plymouth & Pungo Turnpike Road was built and paid for under the supervision of the Literary Fund; the fund now wished to no longer be responsible for maintenance.